Translation Problems of Some Specific Words in the Story “Bemor” by A. Qahhor - Zafar, Allayev (International Journal on Orange Technologies, 2024)
This article describes discusses the translation problems on the work of Abdulla Kahhar named “Patient” and propose alternative variant based on the theory and practice of translation.